Pathologically Relevant Mouse Models for Epstein–Barr Virus–Associated B Cell Lymphoma - Huang, Shiyu; Yasuda, Tomoharu (Frontiers in Immunology, 2021)
The Epstein–Barr virus (EBV) is endemic in humans and can efficiently transform infected B cells under some circumstances. If an EBV carrier experiences immune suppression, EBV+ B cells can turn into lymphoblasts and exhibit growth expansion that may cause lymphoproliferative diseases which often develop into lymphoma. Our immune system conducts surveillance for EBV+ B cells in order to block spontaneous tumor formation. Here, we summarize the EBV products involved in tumorigenesis, EBV-associated lymphomas, and pathologically relevant mouse models. Preclinical mouse models for a range of EBV-associated diseases not only clear the path to new therapeutic approaches but also aid in our understanding of the nature of lymphomagenesis and immune surveillance.